Regulating macrophage glucose metabolism homeostasis via mitochondrial rheostats by short fiber-microsphere scaffolds for bone repair - Zhuang, Pengzhen; Chen, Yu; Zhang, Yu; Yang, Wu; Zuo, Guilai; Rosenholm, Jessica M.; Wang, Zhongmin; Wang, Juan; Cui, Wenguo; Zhang, Hongbo (KEAI PUBLISHING LTD, 2025)
The alterations in glucose metabolism flux induced by mitochondrial function changes are crucial for regulating bone immune homeostasis. The restoration of mitochondrial homeostasis, serving as a pivotal rheostat for balancing glucose metabolism in immune cells, can effectively mitigate inflammation and initiate osteogenesis. Herein, an ion-activated mitochondrial rheostat fiber-microsphere polymerization system (FM@CeZnHA) was innovatively constructed. Physical-chemical and molecular biological methods confirmed that CeZnHA, characterized by a rapid degradation rate, releases Ce/Zn ions that restore mitochondrial metabolic homeostasis and M1/M2 balance of macrophages through swift redox reactions. This process reduces the glycolysis level of macrophages by down-regulating the NF-kappa B p65 signaling pathway, enhances their mitochondrial metabolic dependence, alleviates excessive early inflammatory responses, and promptly initiates osteogenesis. The FM network provided a stable platform for macrophage glycolytic transformation and simulated extracellular matrix microenvironment, continuously restoring mitochondrial homeostasis and accelerating ossification center formation through the release of metal ions from the internal CeZnHA for efficient bone immune cascade reactions. This strategy of bone immunity mediated by the restoration of macrophage mitochondrial metabolic function and glucose metabolic flux homeostasis opens up a new approach to treating bone defects.